1998
DOI: 10.1103/physrevb.57.3253
|View full text |Cite
|
Sign up to set email alerts
|

Nonhydrostatic compression of elastically anisotropic polycrystals. I. Hydrostatic limits of 4:1 methanol-ethanol and paraffin oil

Abstract: The compression of a foil of Cu 3 Au in 4:1 methanol-ethanol and paraffin oil pressure-transmitting media has been studied by energy-dispersive x-ray diffraction in a diamond-anvil cell. Line shifts and line profiles are used to analyze elastic and plastic strains. The increasing viscosity of 4:1 methanol-ethanol causes departures from hydrostatic conditions starting around 7 GPa even while the medium is in a liquid state. The glass transitions in the range 5-7 GPa for paraffin oil and 12-13 GPa for 4:1 methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…The freezing pressure of paraffin oil is around 5 GPa but it is possible to have shear strain for much lower pressures [34]. We observe a change of slope in TM shift under pressure in paraffin oil around 3 GPa.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The freezing pressure of paraffin oil is around 5 GPa but it is possible to have shear strain for much lower pressures [34]. We observe a change of slope in TM shift under pressure in paraffin oil around 3 GPa.…”
Section: Discussionmentioning
confidence: 72%
“…The maximum pressure for good hydrostaticity using paraffin oil is around 4-5 GPa [34]. For argon and 4 :1 methanol ethanol this maximum pressure is around 10 GPa [35].…”
Section: Methodsmentioning
confidence: 97%
“…The (002) peak diminished upon decompression and could not be detected at 2.1 GPa in the loading with the H 2 pressure medium. The reflection could not be associated with any of the known phases in the oil/Ar/H 2 pressure media 39,53,54 or the Fe/Re gasket. The derived LiB 1D y phases are clearly not responsible for the peak either, as the distortions cause an upshift of the dominant (100) peak and appearance of minor peaks at considerably larger angles (Fig.…”
Section: High-pressure Synthesis and Xrd Characterizationmentioning
confidence: 94%
“…19. Otto et al [55] and Sandberg and Sundqvist [56] reported that the glass transitions in 4:1 methanol-ethanol and silicone oil (1cSt) occur at 12-13 and 1.4 GPa, respectively. The hydrostatic limit of the 4:1 methanol-ethanol mixture lies considerably below the pressure of solidification [55].…”
Section: X-ray Diffraction Under Poor Quasi-hydrostatic Conditionsmentioning
confidence: 99%
“…Otto et al [55] and Sandberg and Sundqvist [56] reported that the glass transitions in 4:1 methanol-ethanol and silicone oil (1cSt) occur at 12-13 and 1.4 GPa, respectively. The hydrostatic limit of the 4:1 methanol-ethanol mixture lies considerably below the pressure of solidification [55]. Some part of the deviation from a simple equation of state may also be attributed to the pressure gradient in the sample chamber, so that the pressure at the sample and the measured pressure at the ruby position may differ above the liquid-glass transition.…”
Section: X-ray Diffraction Under Poor Quasi-hydrostatic Conditionsmentioning
confidence: 99%